Optimal social security claiming behavior under lump sum incentives: Theory and evidence - Raimond Maurer; Olivia S. Mitchell; Ralph Rogalla; Tatjana Schimetschek (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2017)
People who delay claiming Social Security receive higher lifelong benefits upon retirement. We survey individuals on their willingness to delay claiming later, if they could receive a lump sum in lieu of a higher annuity payment. Using a moment-matching approach, we calibrate a lifecycle model tracking observed claiming patterns under current rules and predict optimal claiming outcomes under the lump sum approach. Our model correctly predicts that early claimers under current rules would delay claiming most when offered actuarially fair lump sums, and for lump sums worth 87% as much, claiming ages would still be higher than at present.
Keywords: G11; G22; H55; J26; J32; 330; Annuity; delayed retirement; lifetime income; pension; early retirement; Social Security